Process-Based Assessment for Professional Learning in Higher Education: Perspectives on the Student-Teacher Relationship - Bergström, Peter (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
This article reports on a study that was carried out in autumn 2007 with students in a professional nurse education distance course at a Swedish university. The study aimed to develop a greater understanding of the student-teacher relationship based on research questions addressing the teachers’ role, the learning process, and the assessment process in traditional approaches to teaching and learning. A didactical design was adopted, focusing on three learning outcomes in three phases. In each of the three phases, these learning outcomes were assessed by each student documenting his/her knowledge at the beginning, middle, and end of the course. Data was collected via in-depth interviews with students (n = 14) and through a questionnaire (n = 40) and was analysed using an inductive thematic analysis of the material. The results indicate a student-teacher relationship involving ambiguity and complexity in relation to the degree of teacher direction as being teacher-centred or learner-centred and also in relation to the learning process as being reproductive or productive. The interpretation of the results shows diverse aspects of the student-teacher relationship arising from students’ beliefs about teaching, learning, and assessment and, in particular, process-based assessment. The locus of control involves the teachers’ role, the learning process, and the assessment process, which illuminates different perspectives of power relations in the student-teacher relationship.